Environmental tobacco smoke exposure in public places of European cities. Issue 1 (25th February 2005) - Nebot, M; López, M J; Gorini, G; Neuberger, M; Axelsson, S; Pilali, M; Fonseca, C; Abdennbi, K; Hackshaw, A; Moshammer, H; Laurent, A M; Salles, J; et al.
Abstract : Background: Exposure to environmental tobacco smoke (ETS) has important public health implications. The results of the first European multi-centre study that measured ETS exposure in a range of public places (transport, educational settings, and leisure facilities such as bars and restaurants) are presented. Method: Nicotine vapour phase was measured using ETS passive samplers containing a filter treated with sodium bisulfate. Results: Bars and discos are the places with the highest concentrations of nicotine from ETS, median ranging from 19 to 122 μg/m 3 . Restaurants had the next highest values. Concentrations of nicotine generally range from 0.1–5 μg/m 3 in airports, and from 0.5–10 μg/m 3 in train stations. Nicotine was also found in schools and universities, yet schools tended to have the lowest concentrations compared to all the other public places sampled. In hospitals levels were generally below 5 μg/m 3 . Conclusions: Although there is some variability between cities, this study shows that tobacco smoke is present in most of the studied public places. The study also showed that in areas where smoking is prohibited, concentrations of nicotine are lower than in areas where smoking is allowed but they are not zero. The results of this study indicate that policies should be implemented that would effectively reduce levels of tobacco smoke in public areas.